Dada a expressão
(n-2) ! (n+2) !
-------- • --------
(n+3) ! (n-1) !
realize a simplificação.
Soluções para a tarefa
Respondido por
10
(n-2) ! (n+2) ! (n-2)! (n+1).n.(n-1)!
-------- • ------- = -----------------------------------
(n+3) ! (n-1) ! (n+2).[(n+1).n.(n-1)].(n-2)! (n-1)!
_____1
= --------------------------
( n+2).(n-1)
____1
= -------------
n^2+n-2
=[n^2+n-2]^-1
espero ter ajudado!
boa tarde!
-------- • ------- = -----------------------------------
(n+3) ! (n-1) ! (n+2).[(n+1).n.(n-1)].(n-2)! (n-1)!
_____1
= --------------------------
( n+2).(n-1)
____1
= -------------
n^2+n-2
=[n^2+n-2]^-1
espero ter ajudado!
boa tarde!
Perguntas interessantes
Matemática,
10 meses atrás
Português,
10 meses atrás
Matemática,
10 meses atrás
Lógica,
1 ano atrás
Inglês,
1 ano atrás